Research of Ground Waters and their Impacts in Drinking Water, in Some Villages of the Shala Region - Florent, Dobroshi; Armela, Mazrreku; Krenar, Dobroshi; Aziz, Behrami; Ilirjan, Malollari (International Journal of Environment, Agriculture and Biotechnology, 2019)
A large number of natural processes and various anthropogenic activities affect the biological, chemical and physical characteristics of the waters, thus altering the normal values of physico-chemical and bacteriological parameters which followed with the change of its quality.Among the activities that influence the change in water quality are: agricultural activities, industrial activities, mining, waste disposal, urbanization and climate change. Through the development of various industrial activities comes the discharge of various waste during water processes such as: heavy metals, various solvents, toxic sludges and many waste of various kinds. Kosovo has limited water resources either of surface waters or of groundwater, so their rational protection and use is vital for a sustainable economic development of the country. Most of Kosovo's rivers are seasonal rivers that mostly depend on atmospheric precipitation. Village waters in the Shala region in Mitrovica's hydrographic network represent a country's wealth, but the quality of these waters is not satisfactory. First of all, the environmental impact of industrial wastes, industrial plants, mining landfills, agricultural landfills, etc. should be highlighted. The study consists of physico-chemical, bacteriological analysis and determination of heavy metals in underground waters in some villages in the region of Shala (Zhazhë, Maxherë, Boletin, Stantërg, Zjaqë and Vllahi).Physico-chemical and bacteriological analyzes were conducted at the National Institute of Public Health in Mitrovica, whereas the determination of metals was done at the Mining Laboratory with Flotation "Trepça" in Mitrovica. Qualitative assessment consisted of analyzing the most important indicators and comparing them with drinking water standards according to the Standards of Direc. 98/83 EC, WHOs. From the laboratory data it turns out that the water that emanates from these villages is polluted water as a result of high levels of physico-chemical and microbiological parameters, where in some villages the main problem is the presence of bacteria and metals. The source in the well near the elementary school in Stantërg village according to analyzes and the results obtained results as drinking water.